2017
DOI: 10.1128/jvi.01529-16
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A Promotes CD8+T Cell Cytotoxicity To Facilitate West Nile Virus Clearance

Abstract: CD8 ϩ T cells are crucial components of immunity and play a vital role in recovery from West Nile virus (WNV) infection. Here, we identify a previously unrecognized function of interleukin-17A (IL-17A) in inducing cytotoxic-mediator gene expression and promoting CD8 ϩ T cell cytotoxicity against WNV infection in mice. We find that IL-17A-deficient (Il17a Ϫ/Ϫ ) mice are more susceptible to WNV infection and develop a higher viral burden than wild-type (WT) mice. Interestingly, the CD8 ϩ T cells isolated from Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 108 publications
(162 reference statements)
1
45
0
Order By: Relevance
“…Th17-like cells/responses (e.g., IL-17A, IL-21) can enhance the cytotoxicity of CD8 + T cells by enhancing GrB (and A) gene expression, as shown in other conditions (Acharya et al, 2016;Duan et al, 2012). That we observed an increase in IL-17 and IFN-g-producing CD4 + T cells in the brain at 1 week post-TBI, which preceded the increase in GrB + CD8 + T cells at 8 weeks, suggests that Th17 cells may be driving the cytotoxicity of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 87%
“…Th17-like cells/responses (e.g., IL-17A, IL-21) can enhance the cytotoxicity of CD8 + T cells by enhancing GrB (and A) gene expression, as shown in other conditions (Acharya et al, 2016;Duan et al, 2012). That we observed an increase in IL-17 and IFN-g-producing CD4 + T cells in the brain at 1 week post-TBI, which preceded the increase in GrB + CD8 + T cells at 8 weeks, suggests that Th17 cells may be driving the cytotoxicity of CD8 + T cells.…”
Section: Discussionmentioning
confidence: 87%
“…However, we did not observe higher chimerism in PB at days +14 and +21 in Th17 coinjected mice. Data from antitumor and antiviral immunity experiments have also revealed that Th17 cells could have a unique ability to promote CD8 + T cell priming and cytotoxicity in target tissues through both direct [52][53][54] and indirect (via the recruitment of dendritic cells) [52,55] mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that antagonism of CXCR4 significantly improved survival through enhanced intraparenchymal migration of WNV-specific CD8 + T cells within the brain [117]. Moreover, enhanced CD8 + T cells cytotoxicity through a supplement of IL-17A has been shown to increase the survival of the mice from WNV infection [118]. Collectively, the results from these studies indicated that CD8 + T cells play an important protective role in controlling WNV infection.…”
Section: Adaptive Humoral Immunitymentioning
confidence: 91%
“…Although induction of neuroinflammation is necessary for defense against many viral infections, including other flaviviruses, it is also recognized as a potential contributor to neuropathogenesis [159][160][161]. Moreover, levels of some cytokines including IL-2, IL-6, IL-12, granulocyte-macrophage colony-stimulating factor (GM-CSF), IFN-γ, IFN-γ induced protein 10 (IP-10), IL-17A and OPN [30,78,118], have been reported to be elevated for months to years following the recovery of acute illness, leading to a post-infectious proinflammatory state that may contribute to long-term neuroinflammation in WNV survivors [30,78,118]. Among a large cohort of participants with a history of WNV infection in Houston, TX, USA, approximately 40% of those who presented with clinical disease continued to experience WNV-related morbidity up to eight years post-infection [162].…”
Section: Wnv Neuroinvasion and Neuropathogenesismentioning
confidence: 99%